Melatonin and Vitamin D Interfere with the Adipogenic Fate of Adipose-Derived Stem Cells - Basoli, Valentina (Int J Mol Sci, 2017)
Adipose-derived stem cells (ADSCs) represent one of the cellular populations resident in adipose tissue. They can be recruited under certain stimuli and committed to become preadipocytes, and then mature adipocytes. Controlling stem cell differentiation towards the adipogenic phenotype could have a great impact on future drug development aimed at counteracting fat depots. Stem cell commitment can be influenced by different molecules, such as melatonin, which we have previously shown to be an osteogenic inducer. Here, we aimed at evaluating the effects elicited by melatonin, even in the presence of vitamin D, on ADSC adipogenesis assessed in a specific medium. The transcription of specific adipogenesis orchestrating genes, such as aP2, peroxisome proliferator-activated receptor γ (PPAR-γ), and that of adipocyte-specific genes, including lipoprotein lipase (LPL) and acyl-CoA thioesterase 2 (ACOT2), was significantly inhibited in cells that had been treated in the presence of melatonin and vitamin D, alone or in combination. Protein content and lipid accumulation confirmed a reduction in adipogenesis in ADSCs that had been grown in adipogenic conditions, but in the presence of melatonin and/or vitamin D. Our findings indicate the role of melatonin and vitamin D in deciding stem cell fate, and disclose novel therapeutic approaches against fat depots.